Primary school students’ argumentation skills: expression of arguments - Vaiva Schoroškienė (Problemy Wczesnej Edukacji)
This study was conducted to analyze the fourth grade students’ linguistic abilities allowing them to express their arguments in oral and written texts: to determine both the number of presented arguments as well as the level of their elaboration, to characterize the expression of the arguments. The recorded number of participants was 117 fourth-graders from 15 Lithuanian schools. Oral and written texts created by the students were explored in the study. The obtained results revealed that the fourth grade students were able to voice their opinion on at least one argument when they cre-ated an oral or written text on a familiar topic and context. Approximately one-quarter of the study participants were able to present more than three arguments. No significant differences were found between oral and written argumentations with regard to quantity of the arguments. A qualitative analysis of the spoken and written texts indicates that the fourth grade students can use generalized statements (unelaborated secondary statements), they rely on examples and sources. It has also been observed that the study participants’ abilities to develop arguments differ considerably. Their very diverse, even contrasting abilities demonstrate the necessity for developing/updating the curriculum content that would focus more on argumentation.